The Influence of Social Media Utilization, Adversity Intelligence, and Innovation on the Success of Fashion MSMEs in Beringin District, Lubuk Pakam - Ayu Wulan Dari; Adrial Falahi; Rukmini Rukmini; Melisa Zuriani Hasibuan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The purpose of this study is to determine the effect of social media usage, adversity intelligence, and innovation on the success of Fashion MSMEs in Beringin District, Lubuk Pakam. In this study, the data collection technique used a random sampling method, the sample used was 62 respondents. All analyses in this study were assisted by the SPSS 25.0 program. Data analysis techniques were carried out through classical assumption tests, multiple linear regression analysis, and hypothesis testing. Based on the t-test that has been carried out, the results obtained are that the Sig. value of the Social Media Utilization variable is obtained at 0.002<0.05 and the calculated t value (7.513)> t table (1.671). So it can be concluded that the Social Media Utilization variable has a positive and significant effect on the Success variable of MSMEs. Furthermore, the Sig. value of the Adversity Intelligence variable obtained is 0.000 <0.05 and the calculated t value (9.048)> t table (1.671). So it can be concluded that the Adversity Intelligence variable has a significant influence on the MSME Success variable. Furthermore, the Sig. value of the Innovation variable obtained is 0.000 <0.05, which significantly affects the MSME Success variable. From these data, the calculated t value is obtained at (1.167) > t table (1.671). The value of the multiple regression analysis is Y = 9.227+ 0.428 X1 + 0.484 X2 + 0.063 X3 + e. The F-count value is 65.958 with a significance of 0.000 while the F-table value is 2.752. The value of R Square (R2) namely the Value of Social Media Utilization (X1), Adversity Intelligence (X2) and Innovation (X3) is 87.9% while 12.1% is influenced by other variables not studied. Therefore, it can be stated that the Innovation variable has a positive and significant influence on the MSME Success variable.